An engraved surface induces weak adherence and high proliferation of nonadherent cells and microorganisms during culture - Sunil Thomas (BioTechniques, 2020)
When cells are cultured in a Petri dish, the adherent cells attach to the bottom of the dish; whereas, the nonadherent cells float in the culture medium. It was observed that nonadherent cells could be induced to adherent-like cells when cultured in an engraved plastic dish (biosimulator). The adherence of these cells to the engraved surface could be prevented with inhibitors specific for adhesion. It was also observed that culturing microorganisms of the environment in a biosimulator induced weak adhesion and high proliferation. Analysis of the microbiome using 16S rRNA profiling demonstrated that the biosimulator was more efficient in inducing proliferation of several phyla of microorganisms compared with culture by conventional techniques.